2017
DOI: 10.1186/s13014-016-0744-1
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Ki-67 proliferation index and response to radiation therapy in small cell lung cancer

Abstract: BackgroundIn the breast cancer, the decision whether to administer adjuvant therapy is increasingly influenced by the Ki-67 proliferation index. In the present retrospective study, we investigated if this index could predict the therapeutic response to radiation therapy in small cell lung cancer (SCLC).MethodsData from 19 SCLC patients who received thoracic radiation therapy were included. Clinical staging was assessed using the TNM classification system (UICC, 2009; cstage IIA/IIB/IIIA/IIIB = 3/1/7/8). Ki-67 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 23 publications
4
36
0
Order By: Relevance
“…To explain these findings, it was proposed that tumors with increased proliferation may be more prone to the cytotoxic effects of chemoradiotherapy, reminiscent of other highly proliferative tumor types such as lymphoma . Other studies have found a similar association with small cell lung cancer and breast cancer . The findings in this study certainly appear to support this hypothesis.…”
Section: Discussionsupporting
confidence: 77%
“…To explain these findings, it was proposed that tumors with increased proliferation may be more prone to the cytotoxic effects of chemoradiotherapy, reminiscent of other highly proliferative tumor types such as lymphoma . Other studies have found a similar association with small cell lung cancer and breast cancer . The findings in this study certainly appear to support this hypothesis.…”
Section: Discussionsupporting
confidence: 77%
“…A previous study demonstrated that an increased Ki-67 proliferation index may represent a predictive factor for increased tumor radio-sensitivity (36). The present study identified a potential radio-sensitivity indicator for SCLC cell lines following early radiation in vitro.…”
Section: Discussionsupporting
confidence: 50%
“…Previous studies have shown that a high Ki‐67 PI has a negative impact on disease‐free survival, relapse‐free survival, and overall survival in non‐small cell lung cancer . Moreover, the most recent World Health Organization (WHO) classification has adopted the Ki‐67 PI for the diagnosis of small cell lung cancer (SCLC) and a higher Ki‐67 PI may represent a predictive factor for increased tumor radiosensitivity in SCLC . Hence, Ki‐67 may be a valuable biomarker for predicting the prognosis of lung cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Moreover, the most recent World Health Organization (WHO) classification has adopted the Ki-67 PI for the diagnosis of small cell lung cancer (SCLC) and a higher Ki-67 PI may represent a predictive factor for increased tumor radiosensitivity in SCLC. 5 Hence, Ki-67 may be a valuable biomarker for predicting the prognosis of lung cancer patients. The conventional method for detecting Ki-67 expression is immunohistochemistry, which is a test involving invasive biopsy or surgical samples.…”
Section: Introductionmentioning
confidence: 99%